1989
DOI: 10.1111/j.1600-0536.1989.tb04657.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis from dental composite resins due to aromatic epoxy acrylates mid aliphatic acrylates

Abstract: 7 patients were occupationally sensitized to dental composite resin products (DCR): 6 dental nurses and 1 dentist. All had a positive patch test to their DCR. 2 independent types of allergy were seen; (a) aromatic epoxy acrylate, and/or (b) aliphatic acrylates. 4 out of 5 patients reacted to BIS-GMA, the most widely used aromatic epoxy acrylate in DCR, but not the dentist. She and 2 dental nurses were allergic to aliphatic acrylates, including triethylene glycol dimethacrylate (TREGDMA) and triethylene diglyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 30 publications
5
86
0
2
Order By: Relevance
“…BIS-GMA gave a 3 + reaction , and the other two produced a 2 + reaction. A fourth epoxy acrylate, BIS-MA [2,2,-bis(4-(methacryloxy)phenyl)propane], was negative, as were the other 25 (meth)acrylates tested (25). The series of plastics and glues, including cyanoacrylate, was negative.…”
Section: Results and Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…BIS-GMA gave a 3 + reaction , and the other two produced a 2 + reaction. A fourth epoxy acrylate, BIS-MA [2,2,-bis(4-(methacryloxy)phenyl)propane], was negative, as were the other 25 (meth)acrylates tested (25). The series of plastics and glues, including cyanoacrylate, was negative.…”
Section: Results and Case Reportsmentioning
confidence: 99%
“…This finding may indicate cross-reactivity between the test substances. Other possibilities for the concomitant positive reactions with the standard epoxy resin and the epoxy aerylates in patch testing reactions ha ve recently been discussed elsewhere (25,36).…”
Section: Discussionmentioning
confidence: 99%
“…Dermatoses were the most frequently diagnosed adverse response. Kanerva et al (1989) reported hand dermatitis in seven individuals who presented to a dermatology clinic in Finland, six of whom were dental assistants and one a dentist. Four patch-tested positive to bis-glycidyl methacrylate (Bis-GMA) and three to triethylene glycol dimethacrylate (TEGDMA), the two principal resin monomers in most commercially available resin composites.…”
Section: Indirect Evidence For Releaseallergic Responsesmentioning
confidence: 99%
“…Other patients revealed an allergic contact dermatitis to composite resin. The reactions were caused by Bis-GMA and benzoyl peroxide (Carmichael et al, 1997; Kanerva et al, 1989). Seventeen oral lichenoid lesions on the mucosa in contact with composite resin restorations were described by Lind (1998).…”
Section: (Vi) Dentin Adhesives (A) Composition and Release Of Substancesmentioning
confidence: 99%
“…Four of those individuals were hypersensitive to Bis-GMA, and three reacted to TEGDMA; two patients were also hypersensitive to MMA. All of these dental nurses had to stop the practice of their profession (Kanerva et al, 1989).…”
Section: (Vi) Dentin Adhesives (A) Composition and Release Of Substancesmentioning
confidence: 99%